Web search behaviors and infodemic attitudes regarding COVID-19 in Turkey: A framework study for improving response and informing policy on the COVID-19 infodemic - Çalışkan, Cüneyt; Özsezer, Gözde; Pay, Melek; Demir, Gülcan; Çelebi, Ismet; Koçak, Hüseyin (Frontiers in Public Health, 2022)
Objective: This study aimed to develop a framework regarding COVID-19 infodemic response and policy informing through focusing on infodemic concepts circulating on the online search engine in Turkey in relation to the COVID -19 outbreak and comparing the contents of these concepts with Maslow's hierarchy of needs and disaster stages. Materials and Methods: The universe of this descriptive epidemiological research consists of internet search activities on Covid-19 circulating online on Google Trends between March 10, 2020, when the first case was seen in Turkey, and June 01, 2020, when the lockdown restrictions were lifted. Results: There was no internet trend regarding a misinformed attitude within the given date range. While an infodemic attitude towards superficial attitude and racist attitude in the internet environment was detected for one week, an infodemic attitude towards definitive attitude was detected for 2 weeks. The non-infodemic concepts were more common than the other infodemic attitudes. The infodemic concepts were able to reach Maslow's physiological, safety, and social need levels. With the infodemic concepts obtained, a Covid-19 development process framework was developed. The framework consists of three domains (Covid-19, applications and outcomes), including disaster phases and health/social impacts, built on seven public health epochs. Conclusions: A systematized Covid-19 development process framework was modeled in order to conceptualize Covid-19 internet searches and to reveal the development processes and outcomes.